The Wear Behavior of Cross-Linked UHMWPE under Dry and Bovine Calf Serum–Lubricated Conditions - Liza, S.; Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan; Abbas, A.A. (Taylor & Francis, 2013)
The present study was performed to investigate the effects of gamma radiation on the wear behavior of unirradiated and irradiated ultra-high-molecular-weight polyethylene (UHMWPE) against Ti-6Al-4V under dry and lubricated conditions at different applied loads. The UHMWPE specimens were exposed directly to nominal doses of 0, 25, 40, 50, and 100 kGy. Scanning electron microscope (SEM) analysis of the worn surface of UHMWPE and Ti-6Al-4V was performed to understand the mechanism of wear involved between the contact surfaces during wear testing. From the wear test results, there were significant differences between the wear of unirradiated UHMWPE and UHMWPE irradiated at 25, 40, and 50 kGy under dry and lubricated conditions. SEM results for the worn surface of unirradiated and irradiated UHMWPE samples showed that dry and lubricated conditions affected the wear behavior of irradiated UHMWPE. Examination of the Ti-6Al-4V alloy counterface tested under dry conditions revealed that the maximum transfer layer thickness was as high as 22.79 μm. In addition, the UHMWPE irradiated at 100 kGy resulted in a more continuous and adherent transfer film on the Ti-6Al-4V surface compared to the unirradiated sample under dry conditions. Under serum-lubricated conditions, the transfer film layer on the Ti-6Al-4V alloy surface was thinner compared to under dry conditions.